Oksimoron "Failed State" Absennya Negara dan BAngkitnya Gerakan Masyarakat Sipil Menyelamatkan Ruang Publik Pasca Erupsi Merapi - AB Widyanta (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2011)
This study elucidates on strength of social capital in civil society with respect to effort to preserve public space for natural disaster refugees in light of the deterioration of the ability of the state to accomplish civil rights obligation. The analysis began with a study on the characteristics of a failed state. The state can be categorized as failed state if it fulfills three characteristics which are: 1) the negligence in fulfilling civil rights obligations; 2) the disposition of aggressive behaviors; and 3) the intensification of democracy deficit. On the basis of the failed state paradigm, this o the study subsequently moved toward to the focal point, which was that was divided into three parts. The first part examined the paradigm of basic essence in the national constitution and legislation on disasters, relating to public welfare. The second parts discussed the phenomenon of Mt. Merapi's eruption including the chronology of event which in part was responsible for the large number of refugees. The third pat elaborated on the best practice, which where adopted by Posko Mandiri Kadiosoka, as a forum that was established to deal with relief and assistance and service originally intended to fulfill basic rights of refugees. The erosion of social capital capacity in the long term, coupled with and decline in the role of the state as the basic rights handling disasters has seriously limited the independence of civil society in Posko Mandiri Kadiosoko.